Tests and Models of Hydraulic Concrete Material with High Strength - Yajun Wang (Advances in Materials Science and Engineering)
The paper describes an investigation into the comprehensive sensitivities of Sino high strength hydraulic concrete to the addition levels of fly-ash powder and silica fume. Four fly-ash powder addition schemes (100, 120, 140, and 160 kg/m3) and four silica fume addition schemes (12.5, 17.5, 22.5, and 27.5 kg/m3) were considered, respectively. The curing ages’ effects were incorporated in this study. The sensitive feedbacks, including creep development, temperature rise procedure, and strain-stress constitution, have been analyzed. The simulation and test results indicate that the Sino high strength hydraulic concrete, prepared by 140 kg/m3 fly-ash powder and 22.5 kg/m3 silica fume, gives the superb strength, durability, and creep stability.